2006
DOI: 10.1348/135910705x40997
|View full text |Cite
|
Sign up to set email alerts
|

Role of anticipated regret, intentions and intention stability in adolescent smoking initiation

Abstract: Regret and intention stability were shown to be important variables within the TPB in understanding intentions and behaviour of smoking initiation in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 61 publications
6
84
1
4
Order By: Relevance
“…Furthermore, the observed percentage of respondents who indicated a 7 for BI is about 5%. Assuming that a 7 indicates that they will purchase a longevity annuity, this sample proportion is very similar to the share of longevity annuity subscribers (aged [25][26][27][28][29][30][31][32][33][34] in Italy presented in Section 2 (5.2%). Such a result provides evidence that the intention to purchase a longevity annuity found in the present study is fairly in line with the actual behavior at the national level (Whereas in Table 2 the reported data refers to the entire sample (individuals aged [25][26][27][28][29][30][31][32][33][34][35], taking into consideration that the official statistics consider the 25-34 age range, the proportion of those who indicated a 7 for BI has been also calculated excluding 35 years old respondents.…”
Section: Items Constructsmentioning
confidence: 80%
See 2 more Smart Citations
“…Furthermore, the observed percentage of respondents who indicated a 7 for BI is about 5%. Assuming that a 7 indicates that they will purchase a longevity annuity, this sample proportion is very similar to the share of longevity annuity subscribers (aged [25][26][27][28][29][30][31][32][33][34] in Italy presented in Section 2 (5.2%). Such a result provides evidence that the intention to purchase a longevity annuity found in the present study is fairly in line with the actual behavior at the national level (Whereas in Table 2 the reported data refers to the entire sample (individuals aged [25][26][27][28][29][30][31][32][33][34][35], taking into consideration that the official statistics consider the 25-34 age range, the proportion of those who indicated a 7 for BI has been also calculated excluding 35 years old respondents.…”
Section: Items Constructsmentioning
confidence: 80%
“…Specifically, 367,844 of them were aged 25-34 (56.8% males), representing 5.2% of residents aged [25][26][27][28][29][30][31][32][33][34] in the country at the time [11,12]. Despite increase in subscriptions (405,467 and 432,939 in years 2013 and 2014 respectively) [13,14], the amount of longevity annuity purchases by young individuals is claimed to be still negligible [10].…”
Section: The Italian Pension System and Longevity Annuitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…that may bring negative effects to the users as well (Beck L& Ajzen I, 1991). Conner et al (2006) found that the negative attitude, subjective norms and perceptual control on non-smoking can reduce smoking intention (Conner M & Sandberg T, 2006). Positive attitude, subjective norms and perceived behavioural control on alcohol can increase the drinking will (Todd J& Mullan B, 2002).…”
Section: Theory Of Planning Behaviourmentioning
confidence: 99%
“…En el primer caso, aunque la investigación acumulada es aún más bien escasa, se está explorando la utilidad predictiva incremental de factores de influencia social como la norma descriptiva y la percepción de similaridad al prototipo de persona que desarrolla la conducta objeto de estudio (Rivis y Sheeran, 2003a,b;Rivis, Sheeran, y Armitage, 2006;Wilkinson y Abraham, 2004), la percepción de la conducta en términos morales (Godin, Conner, y Sheeran, 2005;McMillan, Higgins y Conner, 2005), o la anticipación de potenciales consecuencias emocionales negativas asociadas a un particular curso de acción (Conner, Sandberg, McMillan y Higgins, 2006). De estas variables, probablemente la de mayor significación para el estudio de la conducta adolescente sea la percepción de la conducta de los iguales y la percepción del grado en que uno se siente similar a la imagen prototípica de quien realiza la conducta, teniendo en cuenta el papel que en esta edad, en la que el individuo está conformando su identidad personal (Erikson, 1968), juegan estos factores de modelado e imitación social (Aloise-Young y Aloise-Young, Hennigan, y Graham, 1996;Barton, Chassin y Presson, 1982;Chassin, Presson, Sherman, Corty y Olshavsky, 1981).…”
Section: Introductionunclassified